Hypothyroidism After Use of Immune Checkpoint Inhibitor Therapy in Patient With Graves' Disease: Cure?. Issue 1 (3rd December 2022) - Sharma, Rajeev
Abstract: Immune checkpoint inhibitors (ICIs) are frequently used as treatment for many malignancies. Immune-related adverse events (irAEs) due to use of ICIs are common. Thyroid involvement is the most common endocrine irAE. Here, we present an unusual case of Graves' disease potentially cured due to destructive thyroiditis caused by inflammation due to ICIs. Thyroid irAEs are more common with programmed cell death protein-1 (PD-1) inhibitor or programmed cell death-ligand 1 (PD-L1) inhibitors than cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) inhibitors. Baseline and serial monitoring of thyroid function tests is recommended.